2013
DOI: 10.1007/s00383-013-3260-5
|View full text |Cite
|
Sign up to set email alerts
|

A report of renal artery embolization for hematuria facilitating neoadjuvant chemotherapy in an unresectable malignant renal rhabdoid tumor

Abstract: Malignant rhabdoid tumor (MRT) of the kidney is a rare pediatric tumor characterized by its aggressive nature and chemoresistance. Our patient had MRT of the right kidney with tumor thrombus in the renal vein, inferior vena cava, and right atrium. He developed transfusion-resistant hematuria. This was successfully controlled with right renal artery embolization allowing completion of his neoadjuvant chemotherapy. He then underwent complete resection of the tumor and thrombus avoiding cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…A pediatric case report highlighted the successful application of renal artery embolization in addressing hematuria associated with a malignant rhabdoid tumor of the kidney. [ 2 ] Another study reported that six pediatric patients with malignancies (three with hemorrhagic cystitis, two with procedure-related internal iliac artery injuries, and one with a tumor rupture) underwent arterial embolization. Five of these patients were successfully treated without complications.…”
Section: Discussionmentioning
confidence: 99%
“…A pediatric case report highlighted the successful application of renal artery embolization in addressing hematuria associated with a malignant rhabdoid tumor of the kidney. [ 2 ] Another study reported that six pediatric patients with malignancies (three with hemorrhagic cystitis, two with procedure-related internal iliac artery injuries, and one with a tumor rupture) underwent arterial embolization. Five of these patients were successfully treated without complications.…”
Section: Discussionmentioning
confidence: 99%
“…Transarterial embolization can be considered a safe primary option for symptomatic or larger AML (Anis et al 2020). In patients with hematuria from renal tumors, such as, malignant rhaboid tumor, embolization can be performed to stop bleeding and facilitate chemotherapy (Sharma et al 2013).…”
Section: Renal and Suprarenal Tumorsmentioning
confidence: 99%